The Dynamic Changes of Transcription Factors During the Development Processes of Human Biparental and Uniparental Embryos - Zhang, Chenxi; Li, Conghui; Yang, Ling; Leng, Lizhi; Jovic, Dragomirka; Wang, Jun; Fang, Fang; Li, Guibo; Zhao, Depeng; Li, Xuemei; Lin, Lin; Luo, Yonglun; et al. (Frontiers in Cell and Developmental Biology, 2021)
Previous studies have revealed that transcription factors (TFs) play important roles in biparental (BI) early human embryogenesis. However, the contribution of TFs during early uniparental embryos development is still largely unknown. Here we systematically studied the expression profiles of transcription factors in early embryonic development and revealed the dynamic changes of TFs in human biparental and uniparental embryogenesis by single-cell RNA sequencing (scRNA-seq). In general, the TFs expression model of uniparental embryos showed a high degree of conformity with biparental embryos. The detailed network analysis of three different types of embryos identified that 10 out of 17 hub TFs were shared or specific-owned, such as ZNF480, ZNF581, PHB, and POU5F1 were four shared TFs, ZFN534, GTF3A, ZNF771, TEAD4, and LIN28A were androgenic specific TFs, and ZFP42 was the only one parthenogenetic specific TF. All the four shared TFs were validated using human embryonic stem cell (hESC) differentiation experiments, most of their target genes are responsible for stem cell maintenance and differentiation. We also found that Zf-C2H2, HMG and MYB were three dominant transcription factor families that appeared in early embryogenesis. Altogether, our work provides a comprehensive regulatory framework and better understanding of TFs function in human biparental and uniparental embryogenesis.